Reflectarray antennas for strategic defense technology - Muhammad Yusof Ismail (Penerbit Universiti Tun Hussein Onn Malaysia, 2012)
This book is designed to present fundamental concepts and principles of reflectarray antenna design for strategic defence technology. The concepts of reflectarray antenna are explained in details relating to its basics on microwave propagation and Maxwell's equations. Basic defence technology is briefly explained for the applicability of reflectarray antennas in defence systems.